Pengembangan produk yoghurt dari santan kelapa dan susu sapi (kajian dari suhu dan lama inkubasi) - Moh Su'i; Mustika Paramitha Cendia; Frida Dwi Anggraeni (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Yoghurt is a probiotic drink from milk that utilizes the performance of the Lactobacillus bulgaricus and Streptococcus thermophilus as starter bacteria. The purpose of this study was to determine the temperature and incubation time and the resulting effect on yoghurt that was produced from milk and coconut milk. Samples for research were treated by incubation temperatures of 25oC, 40oC and 55oC and incubation time of 4 hours, 8 hours and 12 hours with 3 repetitions. The research method was carried out experimentally with a research design using RAK factorial experiments. Data analysis using ANOVA test with a value of = 0.05. The values that resulted in each analysis were pH values 4.26 to 6.36, free fatty acids (FFA) 1.16% to 2.92%, lactic acid 0.35% to 1.21%, N - Amino 0.015% to 0.048% and the total lactic acid bacteria was 3.0 x 106 CFU/ml. While the organoleptic test resulted for the color in a preference value ranged from 3.7 (neutral) – 5 (like), a texture preference value ranged from 3.5 (neutral) – 5 (like), an aroma preference value ranged from 3.8 (neutral) – 4, 4 (slightly like) and taste preferences ranged from 3.2 (neutral) – 5 (like). From the results of the analysis of variance, it was known that yoghurt was made from a mixture of milk and coconut milk had a very significant effect on the pH value, free fatty acid value, lactic acid value and N – Amino value that produced but had no significant effect on sensory test for color, texture, aroma and taste of the yoghurt.